Managing Uncertainty Through Robust-Satisficing Monetary Policy - Q. Farooq Akram; Yakov Ben-Haim; Øyvind Eitrheim (Norges Bank, 2006)
We employ information-gap decision theory to derive a robust monetary policy response to Knightian parameter uncertainty. This approach provides a quantitative answer to the question: For a specified policy, how much can our models and data err or vary, without rendering the outcome of that policy unacceptable to a policymaker? For a given acceptable level of performance, the policymaker selects the policy that delivers acceptable performance under the greatest range of uncertainty. We show that such information-gap robustness is a proxy for probability of policy success. Hence, policies that are likely to succeed can be identified without knowing the probability distribution. We adopt this approach to investigate empirically the robust monetary policy response to a supply shock with an uncertain degree of persistence.
hdl:11250/2498364
Keywords: E31; E52; E58; E61; 330; Knightian uncertainty; monetary policy; info-gap decision theory